Analysis of Community Welfare in the Implementation of the City Minimum Wage: Johns Rawls Justice Approach - Caspari, Andrean; Arman, Arman; Kartiko, Achmad Nur Wahyu; Rizkwanti, Robertha Astri Kurnia Dewi (Public Policy, 2024)
This study is a research to study and analyze the welfare of the people in Tanjung Pinang City in the implementation of the city's minimum wage by using a Critical Study approach, namely Johns Rawls' Justice Theory. Data collection conducted in this study uses Secondary Data by using information sources which include reports, literature books, and other literature sources. The results of this study suggest that community welfare is an important part that must be possessed by everyone in the fulfillment of the Decent Living Needs (KHL) seen from several aspects, namely health, education, employment, housing, consumption, transportation, income and expenses, especially for people in Tanjung Pinang City in the Minimum Wage Implementation. Johns Rawls' Justice Approach highlights the guarantee of freedom for all people, both workers or laborers and disadvantaged communities in certain situations, so that the Tanjung Pinang City Government and the Private Sector provide assistance in the form of training, mentoring and empowerment for disadvantaged communities, and provide rewards to workers or laborers in the form of assistance which includes social security, health insurance, and job safety provided by the Company in accordance with the policies applied by the Tanjung Pinang City Government.